Trade conflicts and credit supply spillovers: Evidence from the nobel peace prize trade shock - Jin Cao; Valeriya Dinger; Ragnar Enger Juelsrud; Karolis Liaudinskas (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
In this paper, we examine how a trade conflict's impact on the real economy can be amplified by financial intermediaries. After the Norwegian Nobel Peace Prize Committee awarded the 2010 Nobel Peace Prize to Chinese dissident Liu Xiaobo, China in practice banned imports of Norwegian salmon. The ban was an unexpected trade shock to the Norwegian salmon industry. Using bank balance sheet and credit register data, we trace how this trade shock affected the lending behavior of banks highly exposed to the salmon industry when the shock occurred. We find that, in the years following the trade shock, highly exposed banks cut back lending to non-salmon firms and households by 3-6 percent more than other banks. Furthermore, we find that the reduction in lending was not driven by the erosion of bank capital, but rather by the shift in expectations about the performance of loans to salmon producers, which drove highly exposed banks to increase their loan loss provisions and reduce risk-taking.
urn:nbn:fi:bof-202210211415
Keywords: F14; G21; 330; trade shock; bank lending channel; expectation shock